2020
DOI: 10.1016/j.fsisyn.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Effective approaches to three-dimensional digital reconstruction of fragmented human skeletal remains using laser surface scanning

Abstract: The preservation and reconstruction of anthropological and archaeological remains has been given considerable attention in recent years, particularly within the fields of forensic science and palaeoanthropology. However, few studies have tapped the potential of using 3D technology to reconstruct, remodel and recontour remains and artefacts for the purpose of human identification. The aim of this study was to use 3D technology for the reconstruction and remodelling of fragmented and missing elements of skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…15 additional articles, referenced in the selected publications, completed the list. From these 39 articles, 33 were primary [3], [4], [24], [25], [31]- [55], [22], [56], [57] and 6 were reviews [2], [7], [11], [14], [58]- [60].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 additional articles, referenced in the selected publications, completed the list. From these 39 articles, 33 were primary [3], [4], [24], [25], [31]- [55], [22], [56], [57] and 6 were reviews [2], [7], [11], [14], [58]- [60].…”
Section: Methodsmentioning
confidence: 99%
“…Considering 3DSS, a total of 12 publications focused on it for VRA of fragments [14], [22], [24], [31], [33], [41], [45], [51], [55]- [57], [67]. Unlike the MDCT-scan that constitutes the first step of the DVI post-mortem examination, 3DSS is too time-consuming for a DVI context, and we did not investigate the parameters used for the acquisition with those scanners.…”
Section: Acquisition Of Mdct-imagesmentioning
confidence: 99%
“…Jani et al found that the application of three-dimensional technology in the reconstruction and description of human bone fragments is less. By analyzing the application of three-dimensional model in forensic cases, the accuracy of three-dimensional reconstruction model is improved from the perspective of anatomical features and digital analysis, and the optimization of three-dimensional reconstruction technology is realized [ 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…26 3D technology has also been proven to be effective in the demonstration of trauma and accident reconstructions. 11,27,28 In fact, 3D printing fracture demonstrations can be used to illustrate the injury process 29,30 as well as aid in restoration of fragmented specimens, that can be more useful in craniofacial identification 8,9 3D digitisation techniques can play an important role in the identification of a cranium through facial reconstruction. 31,32 Forensic artists have produced facial reconstructions of victims using 3D printed skulls from computed tomography (CT) scan data.…”
Section: Applications Of 3d Printing In Forensic Odontologymentioning
confidence: 99%
“…3 With the advent of 3D scanning and printing technology, their applications have been developed across industries such as medicine, dentistry, entertainment, forensic sciences, archaeology, etc. 4,5 3D printing is being used in various forensic science subdisciplines such as anthropology, nursing, crime scene analysis, ballistics, and odontology to produce 3D physical injury models, 6,7 reconstruction of fragmented specimens, 8,9 evidence reconstructions 10 and for demonstration in courts of law. 11,12…”
Section: Introductionmentioning
confidence: 99%